Biocomposite Materials: Tuning Pore Heterogeneity in Covalent Organic Frameworks for Enhanced Enzyme Accessibility and Resistance against Denaturants (Adv. Mater. 19/2019). Issue 19 (7th May 2019) - Sun, Qi; Aguila, Briana; Lan, Pui Ching; Ma, Shengqian
Abstract : Biocatalysis is very appealing for industry, which produces highly selective products with accelerated reaction rates. Immobilization is key to optimizing enzymes in practical processes. In article number1900008, Shengqian Ma and co‐workers describe dual‐pore covalent organic frameworks (COFs) as promising host frameworks for infiltration of enzymes, whereby enzymes are hosted in hexagonal pores and analytes are free to move within triangular pores. In this way, the enzyme encapsulated in the dual‐pore COFs outperforms that in COFs with uniform porosity in terms of activity and resistance to by‐products.